Budidaya Tanaman Sayuran dan Tanaman Obat Keluarga di Pekarangan Berbasis Pertanian Ramah Lingkungan di Kecamatan Sariwangi - Yuni Ertinawati; Selly Purnama; Shinta Rosiana; Ida Wahidah (LPPM UNINUS, 2022)
The potential of agricultural resources is one of the great potentials possessed by Tasikmalaya Regency, especially Sariwangi District. Management of yard land by utilizing the role of women can be a solution in optimizing yard land to increase food yields. The objectives of the activity